Material culture and the circular economy - Rinkinen, Jenny; Shove, Elizabeth (Frontiers in Sustainability, 2023)
Accounts of the circular economy deal with lives of objects mainly through notions of repair, sharing and re-use. This has led to problems associated with contemporary discourses of circularity including the tendency to focus on goods in isolation, and to overlook longer term trends in demand. Drawing from studies of material culture and practice, in this Perspective article we make the case for a more subtle analysis of practices and ‘object relations’. This allows us to engage with basic questions about production, consumption, and the constitution of need – questions that should be integral to contemporary debates about the circular economy, but that are sidelined in what remains classically economistic discussions of substitution, manufacturing, and waste.